A contribution to Centaurea sect. Phaeopappa (Asteraceae, Cardueae) in Iran - Ranjbar, Massoud; Heydari, Razayeh (Phytotaxa, 2015)
Centaurea ardabilica and C. tabriziana, two new species endemic to NW Iran, are described and illustrated. Both new species belong to C. sect. Phaeopappa. Centaurea ardabilica is closely related to C. daralagoezica and is distinguished by having median and upper cauline leaves decurrent, peduncle up to 20 mm long and median and upper cauline leaves often lyrate, and involucres smaller; C. tabriziana is distinguished from C. phaeopappa by having median cauline leaves decurrent, segments of basal cauline leaves in 6–20 pairs, phyllaries with a median appendage 15–22 mm long and a spine up to 10 mm long. An updated key to the species of C. sect. Phaeopappa in Iran is provided.